Impact of Future Work Self on Employee Workplace Wellbeing: A Self-Determination Perspective - Li, Zhongqiu; Yang, Yang; Zhang, Xue; Lyu, Zhuo (Frontiers in Psychology, 2021)
This study examines the association between future work self and employee workplace wellbeing by proposing a moderated mediation model. On the basis of the self-determination theory, self-management is identified as the mediator, and person–organization fit is recognized as the moderator in this study. We collected two waves of data from 239 Chinese employees. The results of the analysis revealed that the future work self is related to greater employee workplace wellbeing, and self-management mediates the links between them. We also found that the person–organization fit strengthens the positive relationship between future work self and self-management, and the indirect effect of future work self on employee workplace wellbeing through self-management. The results of this study extend the antecedents of employee workplace wellbeing and highlight the importance of future work self in current work-related output.